Prof. Dr. Osman Şadi Yenen (1950-2024): Seçkin Bir Bilim İnsanı ve Yurtsever Bir Aydının Ardından. - Eraksoy, Haluk (Klimik Journal / Klimik Dergisi)
Osman Şadi Yenen graduated from İstanbul Faculty of Medicine, İstanbul University, where he studied as a military student, on behalf of the Turkish Naval Force in 1974. In 1981, he became a Specialist in Infectious Diseases and Clinical Microbiology at Gülhane Military Academy of Medicine (GATA). In 1986, he was appointed as Assistant Professor at GATA Haydarpaşa Training Hospital. He passed the exam in 1990 and received the title of Associate Professor. Between 1993 and 2001, he served as Secretary General and President of the Turkish Society of Clinical Microbiology and Infectious Diseases for two terms each. During these years, the Society gained great momentum towards becoming a specialist society. He retired from the Turkish Armed Forces in 1997 and he was appointed to the position of Professor at Department of Microbiology and Clinical Microbiology (later Medical Microbiology), İstanbul Faculty of Medicine, İstanbul University. He took part in the organization of many national and international scientific meetings. Prof. Dr. O. Şadi Yenen has many articles published in Turkish and foreign languages, and he wrote chapters in many books and translated chapters into translated books. He contributed, guided and became a role model for many medical, medical specialty, master and doctoral students he trained. Between 2009 and 2023, he served as a member of the Honorary Committee of the Turkish Society of Clinical Microbiology and Infectious Diseases for seven terms. Between 2011 and 2017, he prepared and presented "Bilim ve Toplum" (the Science and Society) program on Ulusal Kanal television with Prof. Dr. Kürşat Yıldız. In 2016, "Kutup Yıldızı" (the Pole Star) Service Award was presented by the Turkish Blood Centers and Transfusion Association. He retired from his position as a faculty member at İstanbul University on April 11, 2017, due to age limits. He passed away in Muğla on June 8, 2024.